Comparative study of the effectiveness of the surgical technique with and without preservation of the conchal cartilage in otoplasty through the measure of the cephalo-auricular and scapho-conchal angles - Caio Soares; Flávia David João De Masi Nassif; Daniela Dranka; Renata Vecentin Becker; Johann Melcherts Hurtado; Renato da Silva Freitas (2022)
Prominent ear abnormalities affect 5% of the population. A prospective, double-blind study of patients who underwent otoplasty procedures to correct these abnormalities was conducted to compare two surgical techniques. They diverge by the preservation or not of conchal cartilage. The two techniques were compared by measuring the cephalo-auricular and scapho-conchal angles. Measurements were performed in pre and 6-months post-operative periods using alginate molding. Twenty patients were randomly assigned to two groups (with and without cartilage preservation) with 10 participants each. Student's t-test, Covariance Analysis Model (ANCOVA), and non-parametric Mann-Whitney were used in the statistical analyses. A significant reduction in the average of the cephalo-auricular and scapho-conchal angles was observed in both surgical procedures (p<0.001). However, no significant difference was found between them (p=0.887). The two techniques analyzed in this study fulfilled their objectives. Therefore, further comparative studies are needed to confirm the superiority of one over the other. Evidence obtained from at least one properly designed randomized controlled trial.